“ŠTUKA” – BLACK MARKET ON THE TERRITORY OF STARI RAS DURING THE OCCUPATION OF SERBIA IN WORLD WAR II - ŽIVKOVIĆ, Milutin (CURRENTS OF HISTORY, 2019)
The paper is about the emergenc end development of the black market on the territory of Novi Pazar, Tutin, Raška, Sjenica, Nova Varoš, Priboj, Prijepolje, Pljevlja, and Bijelo Polje between 1941 and 1944, the profitability of numerous aspects of illegal trade, the massive participation of the local population of both religions in the various corrupt activities on the market, and the attitude of the occupational and collaborationist authorities as well as liberation movements, with regard to this phenomenon. Summary: As early as 1941, smuggling was already thriving due to the instability of the Italian and German border, the general poverty of the population of Stari Ras, which consequently had already shown a tendency toward illegal forms of trade in the previous decades, as well as the chaos that resulted from the occupation itself. Smuggling soon became widespread in all pores of society, from illegal trade with monopolized commodities and food, weapons, textiles, fuel, alcohol, etc. and the illegal flow of currency. Almost everyone was engaged in black market activity: the local population, both Christian and Muslim, refugees, government officials, customs officers, border guards, Chetniks, Partisans, German, Italian, and Bulgarian soldiers... As a result, the occupational and collaborationist authorities did not do enough to suppress this activity so that it continued to develop, dragging the entire Stari Ras region into even deeper crisis.